Circ-PRMT5 stimulates the proliferative ability in Wilms’ tumor through the miR-7-5p/KLF4 axis: Circ-PRMT5 stimulates the development of Wilms’ tumor - Zhang, Jing; Quan, Yingyu; Su, Xiaoxia; Qiu, Baowei; Dong, Qi (Cellular and Molecular Biology, 2023)
CircRNAs are extensively discovered in mammals and they are closely linked to tumor cell behaviors. This study aims to detect the expression pattern of circ-PRMT5 in Wilms’ tumor and its ability in influencing tumor development. Circ-PRMT5 levels in Wilms’ tumor samples were detected. The regulatory effect of circ-PRMT5 on proliferative ability in Wilms’ tumor cells was assessed by cell counting kit-8 (CCK-8), colony formation and 5-Ethynyl-2’- deoxyuridine (EdU) assay. The interaction in the circ-PRMT5/miR-7-5p/KLF4 axis was determined by luciferase assay. Rescue experiments were conducted to reveal the role of the circ-PRMT5/miR-7-5p/KLF4 axis in Wilms’ tumor development. Circ-PRMT5 was highly expressed in Wilms’ tumor samples. High levels of circ-PRMT5 predicted advanced tumor staging in patients with Wilms’ tumor. Knockdown of circ-PRMT5 markedly suppressed proliferative ability in Wilms’ tumor cells. Luciferase assay confirmed the interaction in the circ-PRMT5/miR-7-5p/KLF4 axis. Rescue experiments finally identified that circ-PRMT5 stimulated the malignant development of Wilms’ tumor by activating the miR-7-5p/KLF4 axis. Circ-PRMT5 is upregulated in Wilms’ tumor samples, which is closely linked to its tumor staging. It stimulates proliferative ability in Wilms’ tumor cells by activating the miR-7-5p/KLF4 axis.